Development of dynamic flow line-monitoring technique to enhance system transparency. (6th April 2007) - Tang, C.S.; Chan, C.Y.; Yung, K.L.
Unpredictable dynamic issues often occur in production activities. Identifying overall operating status is important to trigger the required response, since fluctuations can have a significant effect on logistics-associated functions. However, there are substantial obstacles to getting a good overview of the entire plant operation. Consequently, only piecemeal data are gathered and it is difficult to avoid interpretation discrepancies arising from data filtering. Such a scenario may even introduce negative effects into a system. Traditionally, system dynamics approaches feed signals back to a constructed model and use the difference to drive the system to a balanced stage. For manufacturing management, by recognising the characteristics of the element flows inside a system, it is possible to deduce the process's healthiness. This paper presents a technique to identify the dynamic changes along a flow line-type production.